2015
DOI: 10.1093/annonc/mdv062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotypes of DCIS predict overall and invasive recurrence

Abstract: DCIS molecular phenotype predicts for both overall and invasive recurrence. HER2 testing of DCIS could help clinicians individualise the treatment of patients with DCIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 27 publications
6
80
0
3
Order By: Relevance
“…Although HER2 overexpression is implicated in the pathogenesis of breast cancer (89–91), HER2 is more commonly overexpressed in patients with DCIS (∼27%-56%) (8,12,18) when compared with invasive breast cancer (∼11%-20%) (85,86) (Table 1). The underlying reason why HER2, which is considered to be an important driver of breast cancer (91), is more highly expressed in noninvasive disease, is unclear.…”
Section: Her2mentioning
confidence: 99%
“…Although HER2 overexpression is implicated in the pathogenesis of breast cancer (89–91), HER2 is more commonly overexpressed in patients with DCIS (∼27%-56%) (8,12,18) when compared with invasive breast cancer (∼11%-20%) (85,86) (Table 1). The underlying reason why HER2, which is considered to be an important driver of breast cancer (91), is more highly expressed in noninvasive disease, is unclear.…”
Section: Her2mentioning
confidence: 99%
“…On the other hand, in IBC and DCIS proliferation rate evaluated by Ki67 imunostain recorded different values from low to high rates and it is usualy correlated with tumor grade [30]. Recently, a high KI67 index proved to be an independed prognostic factor, those patients having a high risk for recurrence as IBC [31] HER2neu oncoprotein is one of the four memberes of HER family and plays and important role in cellular growth [32]. If for IBC, the negative impact on prognosis of HER2neu overexpresion is well establised, its role is still debate in DCIS [33].…”
Section: Discussionmentioning
confidence: 99%
“…A more targeted approach to the use of adjuvant therapies following breast conservation for DCIS is also likely to be necessary if women are to receive optimal care. The adoption of molecular phenotyping using ER, HER-2 and Ki67 status [28] or commercially available techniques such as the recently validated Oncotype DX DCIS [29] may help effectively stratify patients and identify those at higher risk of recurrence who may benefit from the addition of adjuvant therapies and those who may be effectively managed by local excision alone. The management of DCIS is an evolving field; identifying areas of uncertainty, developing trials to address these and encouraging clinicians to recruit their patients into new and on-going studies will therefore be necessary if the current controversies are to be addressed and the care for patients improved This study has demonstrated previously significant variability in the current management of DCIS across the UK.…”
Section: Follow-upmentioning
confidence: 99%